Adiciones a la flora marina del Caribe Mexicano - Aguilar Rosas, Luis E.; Aguilar Rosas, Marco A.; Gomez Pedroso Cedillo, Antonio; Fernandez Prieto, Jesús Antonio (Instituto de Ecología, A.C., 1992)
21 spedes and one variety of marine benthic algae are reported for the first time for the Mexican Caribbean on the coast of Quintana Roo, México.